Hydrogeochemical characterization and water quality assessment of mountain springs: Insights for strategizing water management in the lesser Indian Himalayas - Bhargabnanda Dass; M. Someshwar Rao; Sumit Sen (Journal of Hydrology: Regional Studies)
Study region: Lesser Himalayas, Paligad watershed, Tehri-Garhwal, Uttarakhand, India Study focus: This study evaluates the hydrogeochemical characteristics and water quality of a mountainous spring watershed in the data-scarce Indian Himalayan region, where communities face severe water scarcity. Despite these challenges, comprehensive understanding of hydrogeochemical process dynamics affecting these water sources remains limited. We employed an integrated approach combining hydrogeochemical analysis, multivariate statistics, and spring water quality index modeling to understand the dominant processes influencing aquifer hydrochemistry and assess spring status, providing a reference framework for regional water management decision-makers. New hydrological insights for the region: Results reveal strong spatio-temporal variations in spring aquifer chemistry, primarily influenced by silica degradation and groundwater mixing, with secondary effects from ion-exchange and anthropogenic activities. Silicate and carbonate mineral weathering shapes groundwater chemical evolution, with Ca–HCO3 and Ca-Mg-HCO3 as major hydrochemical facies. Significant variations in key ions (Ca²⁺, Mg²⁺, HCO₃⁻, K⁺) across spring, stream, and river sources indicate diverse geochemical processes influenced by local geology and hydrology. A novel Spring Water Quality Index (SWQI) was developed to intuitively evaluate and manage spring quality variations. This work provides a first-hand systemic assessment to address the increasing vulnerability of Himalayan spring water sources to natural and human-induced factors.